Spatial and temporal distributions of water physicochemical, sediment quality and sedimentation in Sembrong Reservoir - Baharim, Nor Bakhiah (2015)
Understanding the characteristics of a reservoir ecosystem is crucial in water resources management. The aims of this study are to investigate the limnological characteristics and spatial physicochemical properties of water quality in the Sembrong Reservoir. This study includes investigation of spatial variability of sediment properties and the quality of bottom sediment and long term sedimentation rate in relation to land use change and major hydrology events. The data collection was carried out from November 2011 to January 2013. Vertical sampling of reservoir water was conducted and its physical properties were measured in situ. Water samples were also analysed in laboratory for Al, Fe, K, Na, Mg, Ca, Fe, Mn, Zn, Cu, As, Pb and Total Phosphorous. Stable isotopes (18O and 2H) were measured using SERCON GEO 20–20 Continuous Flow Isotope Ratio Mass Spectrometer (CF–IRMS). A total of nine sediment cores were analysed for fallout 210Pb and 137Cs radioisotopes activities by Gamma Spectrometer. Sediment samples were also analysed for Total Carbon and Total Nitrogen and grain size distribution. Polymictic pattern was observed in this reservoir, especially during wet months. Thermal stratification occurred at depths between 3m and 4 m. The occurrence of photosynthesis at depth less than 3m increased phytoplankton productions. Manganese (Mn) and iron (Fe) concentrations were subjected to geochemical processes, particularly redox reaction. The mean concentrations of heavy metals in the water column decreased in the following order: Fe > Mn > Zn > Cu > As > Pb. Based on Carlson’s Trophic State the Sembrong Reservoir is classified as hypereutrophic. On the other hand, the heavy metal concentrations as determined by the Heavy Metal Evaluation Index (HEI) fall under slightly polluted to polluted. Factor analysis suggested that the heavy metals are originated from modern agricultural plots. Higher heavy metal contents were observed in the west wing. This could be associated with micronutrient fertilizer from oil palm plantation with remarkable increases in the Enrichment Factor and Geoaccumulation Index for Zn, Cu, and Mn. Sediment mixing and digenesis processes influenced the deposition of bottom sediment. Given the irregularities of 210Pb, long-term sedimentation rates were calculated by dividing the sediment thickness over a period. Higher sedimentation rates were observed at cores S1 and S6A with sedimentation rates of 1.10 and 1.17 cm/year, respectively. Forest clearing for oil palm plantation, dam development, and modern agricultural activities play important roles in the spatial and temporal distributions of sediment and water quality. This study highlighted the importance of limnology in controlling the physical and chemical processes in a reservoir ecosystem. The physicochemical properties of sediment also significantly influence the quality of reservoir ecosystem. Therefore, a comprehensive management plan to preserve the reservoir ecosystems is needed to ensure the sustainability of water resources.